2014
DOI: 10.15408/ess.v4i1.1957
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH RASIO PROFITABILITAS, RASIO AKTIVITAS, RASIO PASAR, FIRM SIZE, TINGKAT SUKU BUNGA, DAN NILAI TUKAR TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan Makanan dan Minuman Di Bursa Efek Indonesia Periode 2008-2011)

Abstract: Penelitian ini bertujuan untuk menganalisis pengaruh Rasio Profitabilitas, Rasio Aktivitas, Rasio Pasar, Firm Size, Tingkat Suku Bunga dan Nilai Tukar terhadap Return Saham Perusahaan Makanan dan Minuman di Bursa Efek Indonesia. Sampel yang digunakan adalah perusahaan makanan dan minuman yang terdaftar di Bursa Efek Indonesia selama periode 2008 – 2011, total sampel yang digunakan berjumlah 44 sampel.Metode pengambilan sampel dengan Purposive Sampling.Model analisis yang digunakan dalam penelitian ini adalah r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This study is in line with research conducted by Rosiana et al (2014) which states that firm size has no effect on stock returns. And research conducted by Dewi & Ratnadi (2019) state that the firm size variable partially has a negative and insignificant effect on stock returns.…”
Section: Effect Of Firm Size On Stock Returnsupporting
confidence: 92%
“…This study is in line with research conducted by Rosiana et al (2014) which states that firm size has no effect on stock returns. And research conducted by Dewi & Ratnadi (2019) state that the firm size variable partially has a negative and insignificant effect on stock returns.…”
Section: Effect Of Firm Size On Stock Returnsupporting
confidence: 92%
“…Several previous studies conducted by Elia [6] showed no influence between current ratio and stock returns. The results of the research conducted by Giovani [7], Agung [8], Michael aldo [9], and Dwi Budi [10], Minanari [11] showed the influence of Return On Equity on stock return, while Elia's research [12] and Rita [13] shows that there is no influence between Return On Equity and stock returns. The results of previous studies conducted by Umrotul [14], and Noviansyah [15] showed the effect of Firm Size on Retun shares, while the Fuji [16] study and Rita [13] showed no influence between Firm Size and stock returns.…”
Section: Introductionmentioning
confidence: 99%